Calculations of the Thermal Regime of Earthen Dams Considering Their Construction by Layers (Raschet Termicheskogo Rezhima Zemlianykh Plotin s Uchetom Posloinogo ikh Vozvedeniia) - Shugaeva,R T (1976)
The planning and construction of water engineering structures under severe climatic conditions place increased requirements on investigation of the thermal regime of these structures, both during the period of construction and the period of use. A detailed study is presented investigating a number of calculations in the determination of the thermal regime of impervious earthern dams and their bases during the period of construction and the first years of use considering the fact that they are constructed in layers. These calculations can be reduced to solution of the problem of freezing and thawing of soils in areas of complex configuration, the dimensions of which change during the process of calculation. (Author) Trans. of Izvestiya Vsesoyuznogo Nauchno-Issledovatel'Skogo Instituta Gidrotekhniki v96 p218-224 1976.